Trypanocidal activity of mastoparan from Polybia paulista wasp venom by interaction with TcGAPDH - Chagas Vinhote, Juliana Freire (2017)
Chagas disease, considered a neglected disease, is a parasitic infection caused by Trypanosoma cruzi, which is endemic throughout the world. Previously, the antimicrobial effect of Mastoparan (MP) from Polybia paulista wasp venom against bacteria was described. To continue the study, we report in this short communication the antimicrobial effect of MP against Trypanosoma cruzi. MP inhibits all T. cruzi developmental forms through the inhibition of TcGAPDH suggested by the molecular docking. In conclusion, we suggest there is an antimicrobial effect also on T. cruzi. (C) 2017 Elsevier Ltd. All rights reserved.